2020
DOI: 10.1177/0218492320983464
|View full text |Cite
|
Sign up to set email alerts
|

Results of reconstructive interventions in patients with ischemic cardiomyopathy

Abstract: Background Effective treatment of patients with ischemic cardiomyopathy is one of the most difficult issues in contemporary cardiac surgery. The aim of this study was to evaluate the long-term effectiveness of reconstructive interventions on the left ventricle during chronic heart failure in patients with ischemic cardiomyopathy. Methods Between March 2013 and December 2017, 178 patients underwent surgical treatment for ischemic cardiomyopathy. Isolated coronary artery bypass grafting was compared with coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The pathogenesis of ICM is still not fully understood. Several studies (10,11) have shown that inflammation, apoptosis, myocardial fibrosis, and other pathological changes play an important role in the occurrence and development of ICM. We present the following article in accordance with the STREGA reporting checklist (available at https://jtd.amegroups.com/article/ view/10.21037/jtd-22-1060/rc).…”
Section: Original Articlementioning
confidence: 99%
“…The pathogenesis of ICM is still not fully understood. Several studies (10,11) have shown that inflammation, apoptosis, myocardial fibrosis, and other pathological changes play an important role in the occurrence and development of ICM. We present the following article in accordance with the STREGA reporting checklist (available at https://jtd.amegroups.com/article/ view/10.21037/jtd-22-1060/rc).…”
Section: Original Articlementioning
confidence: 99%
“… 2 Ischemic cardiomyopathy (ICM) is linked to myocardial insufficiency and inadequate perfusion caused by obstructive CAD. 3 Furthermore, end-stage HF frequently stems from ICM, which can result in a significant decrease in the left ventricular ejection fraction (LVEF). 4 , 5 HF refers to clinical syndromes characterized by pulmonary and/or body circulation stasis.…”
Section: Introductionmentioning
confidence: 99%